Accuracy of virtual surgical planning of orthognathic surgery with aid of CAD/CAM fabricated surgical splint—A novel 3D analyzing algorithm - Chin, Shih-Jan; Wilde, Frank; Neuhaus, Michael; Schramm, Alexander; Gellrich, Nils-Claudius; Rana, Majeed (Journal of cranio-maxillo-facial surgery, 2017)
The benefit of computer-assisted planning in orthognathic surgery has been extensively documented over the last decade. This study aims to evaluate the accuracy of a virtual orthognathic surgical plan by a novel three dimensional (3D) analysis method. Ten patients who required orthognathic surgery were included in this study. A virtual surgical plan was achieved by the combination of a 3D skull model acquired from computed tomography (CT) and surface scanning of the upper and lower dental arch respectively and final occlusal position. Osteotomies and movement of maxilla and mandible were simulated by Dolphin Imaging 11.8 Premium® (Dolphin Imaging and Management Solutions, Chatsworth, CA). The surgical plan was transferred to surgical splints fabricated by means of Computer Aided Design/Computer Aided Manufacturing (CAD/CAM). Differences of three dimensional measurements between the virtual surgical plan and postoperative results were evaluated. The results from all parameters showed that the virtual surgical plans were successfully transferred by the assistance of CAD/CAM fabricated surgical splint. Wilcoxon's signed rank test showed that no statistically significant deviation between surgical plan and post-operational result could be detected. However, deviation of angle U1 axis–HP and distance of A–CP could not fulfill the clinical success criteria. Virtual surgical planning and CAD/CAM fabricated surgical splint are proven to facilitate treatment planning and offer an accurate surgical result in orthognathic surgery.